Examining Transfer Effects of Dual-Task Training Protocols for a Complex Locomotor Task. - Worden, Timothy A.; Vallis, Lori Ann (Journal of Motor Behavior)
Training protocols designed to improve dual-task performance of an obstacle crossing and auditory Stroop task (OBS+Stroop) were tested. In Experiment  1 , following baseline collection of OBS+Stroop trials, proximally related walking training was performed, and participants were then retested on the OBS+Stroop test. After training, participants adopted a more cautious obstacle crossing strategy, indicating a potentially safer navigation strategy. Transfer effects from distally related training were then examined (Experiment  2 ); a computer game training paradigm was examined using the same testing protocol as Experiment  1 . Computer training demonstrated improved dual-task performance on some measures, but did not induce a more cautious stepping strategy. Results indicate that dual-task training needs to be similar to targeted tasks to yield reliable, positive training outcomes.